Non-Canonical, Extralysosomal Activities of Lysosomal Peptidases in Physiological and Pathological Conditions: New Clinical Opportunities for Cancer Therapy - Ryan Conesa-Bakkali; Macarena Morillo-Huesca; Jonathan Martínez-Fábregas (Cells)
Lysosomes are subcellular compartments characterised by an acidic pH, containing an ample variety of acid hydrolases involved in the recycling of biopolymers. Among these hydrolases, lysosomal proteases have merely been considered as end-destination proteases responsible for the digestion of waste proteins, trafficked to the lysosomal compartment through autophagy and endocytosis. However, recent reports have started to unravel specific roles for these proteases in the regulation of initially unexpected biological processes, both under physiological and pathological conditions. Furthermore, some lysosomal proteases are no longer restricted to the lysosomal compartment, as more novel non-canonical, extralysosomal targets are being identified. Currently, lysosomal proteases are accepted to play key functions in the extracellular milieu, attached to the plasma membrane and even in the cytosolic and nuclear compartments of the cell. Under physiological conditions, lysosomal proteases, through non-canonical, extralysosomal activities, have been linked to cell differentiation, regulation of gene expression, and cell division. Under pathological conditions, these proteases have been linked to cancer, mostly through their extralysosomal activities in the cytosol and nuclei of cells. In this review, we aim to provide a comprehensive summary of our current knowledge about the extralysosomal, non-canonical functions of lysosomal proteases, both under physiological and pathological conditions, with a particular interest in cancer, that could potentially offer new opportunities for clinical intervention.